2000
DOI: 10.1055/s-2000-7009
|View full text |Cite
|
Sign up to set email alerts
|

Pseudostenokardie bei Belastung durch »Elektrosmog«

Abstract: The results of the test showed that there was no causal relation between the patient's angina-like-symptoms and electromagnetic fields. The phenomenon of electrosensitivity was probably caused by psychological mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Prior research trying to find evidence for the existence of electrosensitivity concentrated on three types of research. First, subjectively electrosensitive people and healthy controls were examined concerning their ability to detect EMFs of a given strength in double blind provocation studies [Andersson et al, 1996;Toomingas, 1996;Barth et al, 2000;Flodin et al, 2000;Lonne-Rahm et al, 2000;Lyskov et al, 2001b;Hietanen et al, 2002]. A typical result of these trials was that neither group was able to detect EMFs at nonrandom hit rates.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research trying to find evidence for the existence of electrosensitivity concentrated on three types of research. First, subjectively electrosensitive people and healthy controls were examined concerning their ability to detect EMFs of a given strength in double blind provocation studies [Andersson et al, 1996;Toomingas, 1996;Barth et al, 2000;Flodin et al, 2000;Lonne-Rahm et al, 2000;Lyskov et al, 2001b;Hietanen et al, 2002]. A typical result of these trials was that neither group was able to detect EMFs at nonrandom hit rates.…”
Section: Introductionmentioning
confidence: 99%
“…No statistically significant effects for other factors of well-being (good mood and alertness). No statistically significant interaction between exposure and group of participants (IEI-EMF or controls) Barth [70]1 IEI-EMFMobile phone (no information about exposure level, only that the mobile phone was switched “on” or “off”)15 exposure trials, 16 sham trials; exposure duration and interval between trials not indicated;double-blind studyVerbal report of experiencing any of 4 symptoms during a trial: palpitations, chest pain, vertigo, prickling in the armNo statistically significant effect of exposure Eltiti et al [21]44 IEI-EMF,114 controlsGSM 900 MHz, GSM 1800 MHz, UMTS base station signals; combined power flux density of 10 mW/m 2 for GSM signal, 10 mW/m 2 for UMTS signal2 exposure sessions to GSM (combined signal of GSM 900 and GSM 1800 frequencies) or UMTS signal and 1 sham session, each 50 min; sessions were separated by at least 1 week;double-blind studyAssigned scores on a 100-mm VAS for rating the severity of 6 symptoms (anxiety, tension, arousal, relaxation, discomfort, and fatigue); assigned levels on symptom scales consisting of a list of 57 symptoms extracted from the Electromagnetic Hypersensitivity Questionnaire [6]For individuals with IEI-EMF: elevated levels of arousal when exposed to a UMTS signal ( p < 0.0025), likely due to a non-balanced design (45% of participants had UMTS exposure in the first of the three sessions): no statistically significant effect when conditions were compared for each session separately; no statistically significant effect for the 6 other items of subjective well-being, nor for symptoms Furubayashi et al [36]11 IEI-EMF, 43 controls2.14 GHz WCDMA base station signal with power density of 0.265 W/m 2 ; EF at the subjects’ head: 10 V/m, calculated brain SAR 10g peak : 0.0078 W/kg1 session with continuous exposure, 1 session with intermittent exposure with EMF turned “on” and “off” randomly every 5 min (50% of the time "on"), 1 sham session, 1 noise session, each 30 min; two sessions on 1 day; sessions were separated by at least 2 h;double-blind studyAssigned level of discomfort on a 5-point scale; assigned scores on a 5-point scale in the Profile of Mood States (POMS) questionnaire [71] for rating the severity of 6 states of mood (tension-anxiety, anger-hostility, depression, vigor, fatigue, confusion)No statistically significant effect of exposure Hietanen et al [57]20 IEI-EMFAnalogue 900 MHz NMT phone (output power: 1 W), digital GSM phone 900 MHz (output power: 0.25 W), digital GSM phone 1800 MHz (output power: 0.125 W); power densities: 2–200 W/m 2 3 exposure sessions to different signals, 1 sham session, each 30 min; sessions were separated by at least 60 min;double-blind studyVerbal report of any symptoms and sensations experienced during a trialHigher number of symptoms was reported for the sham condition than for any of the RF exposures. Statistical significance ( p < 0.05) of this effect was explicitly specified only for men. Hillert et al [39]38 IEI-EMF, 33 controls884 MHz GSM mobile phone-like signal, head (calculated): SAR 10g average...…”
Section: Resultsmentioning
confidence: 99%
“…From the reviewed studies there is at present no reliable evidence for an effect of exposure. Nine of the included studies in this review suggested that a nocebo effect may explain the development of symptoms [22, 39, 59, 64, 65, 70, 7779]. The symptoms correlated with beliefs and knowledge about being exposed, and this has been easy to demonstrate in experimental studies while it proved difficult to find reliable evidence for a physical relation between EMF exposure and health complaints.…”
Section: Discussionmentioning
confidence: 97%